2010
DOI: 10.4103/0970-2113.71944
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium and stable asthma: Is there a link?

Abstract: Background:Although magnesium is used through intravenous and inhalation route in the management of asthma, actual prevalence of hypomagnesemia in asthma is not known. We conducted this study: 1) to detect the prevalence of hypomagnesemia in stable asthma and 2) to assess the significance of hypomagnesemia in these patients.Design:Prospective clinical study.Setting:Department of Respiratory Medicine, Calcutta National Medical College, Kolkata.Period of Study:Four months from January, 2007, to April, 2007.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
3
15
0
1
Order By: Relevance
“…This was in agreement with Das et al [17], who reported that there is statistically significant relationship of hypomagnesemia with the use of LABA, (p value = 0.003) and with the use of P3 medications, (p value = 0.007). In the same study Das et al [17], showed a statistically significant relationship of hypomagnesemia with use of ICS, (p value = 0.021) and explained this by increased urinary loss of magnesium as a side-effect of therapy with corticosteroid [9].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was in agreement with Das et al [17], who reported that there is statistically significant relationship of hypomagnesemia with the use of LABA, (p value = 0.003) and with the use of P3 medications, (p value = 0.007). In the same study Das et al [17], showed a statistically significant relationship of hypomagnesemia with use of ICS, (p value = 0.021) and explained this by increased urinary loss of magnesium as a side-effect of therapy with corticosteroid [9].…”
Section: Discussionsupporting
confidence: 94%
“…This result was in agreement with Alamoudi [13] who reported that the number of hospitalizations in chronic asthmatics with low Mg (40%) was significantly higher than that found in chronic asthmatics with normal Mg (11.8%), (p value = 0.04) and Das et al [17], who reported that there is statistically significant relation between serum Mg levels (normo or hypo) and previous and future exacerbations, (p value = 0.019). This can be explained that low serum Mg may increase airway hyper-reactivity, and hyper-responsiveness which renders chronic asthmatics with low Mg more prone to develop bronchoconstriction and acute exacerbations of asthma.…”
Section: Discussionsupporting
confidence: 91%
“…Low serum Mg levels in adult asthmatic patients have been described many years ago (9,29). Contrarily, some studies reported no difference between asthmatic patients and normal individuals, in terms of serum magnesium levels (10,11).…”
Section: Eurasianmentioning
confidence: 98%
“…As intracellular electrolyte measurement tests are expensive, they are not easily available and difficult for clinical application (29). Therefore, generally serum Mg levels are used for the monitoring of changes in body Mg concentration during acute attack and stable phases of asthma.…”
Section: Eurasianmentioning
confidence: 99%
“…This is the first study to assess the effects of hypomagnesemia on PFT of asthmatic patients. Mg 2+ replacement treatment was not effective in chronic asthmatic patients in previous studies [1,19]. In an epidemiological study, reduced intake of Mg 2+ was associated with hyperreactivity of the airways to methacholine.…”
Section: Discussionmentioning
confidence: 99%